A Multi-Criteria Evaluation of Sustainable Olympic Events: Integrating AHP, EWM, and Natural Breaks - Young, Victor Niu; Young, Forest Niu (Transactions on Computer Science and Intelligent Systems Research, 2025)
Facing the sustainable development challenges of Olympics, this study aims to identify the Sports, Disciplines, or Events (SDEs) that best align with the Olympic spirit and the International Olympic Committee’s (IOC) long-term strategy. All 47 SDEs held between 1896 and 2028 were evaluated using the IOC’s six Sports Inclusion Criteria (C1–C6) as primary indicators, each subdivided into 3-4 secondary factors (21 total). Subjective weights for P1–P21 were derived via the Analytic Hierarchy Process (AHP), objective weights via the Entropy Weight Method (EWM), and comprehensive weights using the Linear Weighted Average Method (LWAM, α = 0.5). Normalized indicator data were used to compute overall SDE scores, which were then classified into 5 strategic groups using the Natural Breaks (NB) method. Breakpoints were identified at 0.7823, 0.7689, 0.6503, 0.5983, and 0.3128. Swimming ranked highest (0.7823) as an elite event, followed by gymnastics (0.7689) and athletics (0.7641), while Roque (0.3128) and Basque Pelota (0.5326) were considered outdated or alternative. This study introduces the AHP-EWM approach to sports event evaluation for the first time, creating the AHP-EWM-NB comprehensive model for sustainable assessment and strategic grouping of Olympic SDEs. The model fills a research gap and provides a data-driven decision-making tool, expanding the application of multi-criteria decision-making (MCDM) in sports management.